THE INFLUENCE OF THE FAMILY ENVIRONMENT ON THE DEVELOPMENT OF GENERATION ALPHA IN BANDUNG CITY AND BANDUNG REGENCY, WEST JAVA - Sakroni (Adisam Publisher, 2024)
This study aims to explore the influence of the family environment on the development of children from Generation Alpha in Bandung City and Bandung Regency. Using a quantitative design, this research involved 300 respondents, consisting of children aged 5 to 14 years and their parents. Data collection methods included questionnaires, semi-structured interviews, and direct observations. The findings indicate that family structure, parenting style, communication quality, and emotional support from the family significantly impact children’s cognitive, social, and emotional development. Statistical analysis revealed that children from nuclear families had higher cognitive scores, authoritative parenting was associated with improved social skills and emotional well-being, and good communication and emotional support were linked to reduced stress and increased happiness. This study emphasizes the importance of creating a stable and supportive family environment to support the optimal development of Generation Alpha children and provides recommendations for family practices and future research.